CuO NANOPARTÍCULAS: UM EFICENTE E RECICLÁVEL CATALISADOR PARA REAÇÕES DE ACOPLAMENTO CARBONO-SELÊNIO - Santos, Cayane Genro (2009)
ABSTRACT Title: CuO Nanoparticles: An Efficient and Recyclable Catalyst for Cross-Coupling Reactions C-Se Author: Cayane Genro Santos Academic Advisor: Prof. Dr. Diego Alves In this work, we present an efficient cross-coupling reaction of organic diselenides 1 with aryl boronic acids 2 using a catalytic amount of CuO Nanoparticles (CuO NPs), without any ligand and additive in the presence of air atmosphere. The method gives the corresponding products 3 in good to excellent yields. Ar - Se - Se - Ar + Ar¹B(OH)2 CuO NPs solvent temperature Ar - Se - Ar¹ 1 2 3 Ar, Ar¹ = Aryl Our initial studies have focused on the development of an optimum set of reaction conditions. After that, these reactions were performed with organic diselenides and aryl boronic acids bearing electron-withdrawing and electrondonating groups. We employed the same reaction condition for the tellurium. The products were obtained in satisfactory yields. At the end, we check the recyclability of the catalyst. The catalyst were recovered by centrifugation and reused for 4 catalytic reactions. The catalyst maintained its good level of activity even after being recycled four times.